THE PATHWAY FROM ONLINE GAMING TO ONLINE GAMBLING; DETERMINANTS OF STUDENTS’ DECISION-MAKING - Asep Rudi Nurjaman; Asep Totoh; Dani Wardani (PEDAGOGIK : JURNAL PENDIDIKAN, 2025)
Online gaming’s rapid growth has introduced gambling-like mechanics (e.g., loot boxes, gacha systems), raising concerns about their influence on students’ susceptibility to online gambling. Despite increasing global attention, little research explores how these gaming elements normalize gambling behaviors among adolescents, particularly in educational contexts. This study addresses this gap by examining whether prolonged exposure to online gaming—especially games with gambling mechanics—increases students’ risk of engaging in online gambling. Using a mixed-method approach, this study combined surveys of 177 students and in-depth interviews with 35 students from SMK Bakti Nusantara 666 to analyze gaming habits, psychological effects, and exposure to gambling elements. Findings revealed that excessive gaming, particularly in games with loot boxes or gacha systems, correlated with higher gambling tendencies, addiction risks, academic decline, and social isolation. Conversely, moderate gaming offered benefits like stress relief. The study underscores the urgency of preventive measures, such as school policies, parental controls, and curriculum-integrated gambling awareness programs. It also highlights the need for collaboration among educators, parents, and digital platforms to mitigate risks.